Contracting with Externalities and Outside Options - Francis Bloch; Armando Gomes (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper proposes a model of multilateral contracting where players are engaged in two parallel interactions: they dynamically form coalitions and play a repeated normal form game with temporary and permanent decisions. This formulation encompasses many economic models with externalities and outside options. We show that when outside options are pure (i.e. independent of the actions of other players), there exists a Markov Perfect equilibrium resulting in efficient outcomes when players become perfectly patient. If outside options are not pure, all Markov perfect equilibria may be inefficient. The distribution of coalitional gains and the dynamics of coalition formation are characterized in four illustrative applications.
Keywords: C71; C72; C78; D62; 330; Outside options; Externalities; Coalitional bargaining; Verhandlungstheorie; Vertragstheorie; Koalition; Theorie; Normalformspiel